The impact of participating in an activity programme (10,000 steps @ work lite programme) on dietary change : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Nutritional Science at Massey University, Palmerston North, New Zealand - Hartshorn, Nikki (Massey University, 2009)
High levels of diet related chronic disease in New Zealand has lead to the development of health promotion programmes. The work place is an important venue to implement health promotion programmes to encourage staff to make healthy lifestyle choices. The aim of this research is to examine if a physical activity programme may be a ‘gateway’ to other positive behavioral changes such as healthy eating and/or cutting down smoking. This research introduces a health promotion programme to employees at a call centre. The intervention involved 3 groups: the health promotion group (HPG), which received both the physical activity programme (10,000 steps @ work ‘lite’ programme) plus nutritional information; the nutritional group (NG), which received only the nutritional information and the control group (CG), which did not take part in the intervention. The impact of the nutritional seminars with or without the exercise programme was measured by the participants’ reported fruit, vegetable, snack consumption and transtheoretical stages of change for exercise, fruit and vegetable intake, healthy snacking and smoking. A questionnaire was used to collect data retrospectively. The health promotion group (HPG) made positive changes in all behaviours unlike the nutritional group (NG) and the control group (CG). This provides some support for the hypothesis that physical exercise may act as a ‘gateway’ to other positive behavioural changes.
Keywords: Health promotion; Physical activity; Nutrition; Exercise programme; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321216 Health promotion